BOOK REVIEW Professor Muhammad Munir, Rights of the Child in Islam: Theory, Mechanisms, Practices and Convention on the Rights of the Child (Islamabad, Iqbal Institute for International Research and Dialogue (IRD), Islamic Research Institute Press, International Islamic University, Islamabad, 2017), 283 Pages, ISBN: 978-969-7576-08-1). Issue 2 (2018) - Iqbal, Khurshid
No abstract available